Cloning of the Rhesus Lymphocryptovirus Viral Capsid Antigen and Epstein-Barr Virus-Encoded Small RNA Homologues and Use in Diagnosis of Acute and Persistent Infections - Rao, Pasupuleti (American Society for Microbiology, 2000)
Epstein-Barr virus (EBV) is the most common cause of infectious mononucleosis and is associated with the development of several human malignancies. A closely related herpesvirus in the same lymphocryptovirus (LCV) genera as EBV naturally infects rhesus monkeys and provides an important animal model for studying EBV pathogenesis. We cloned the small viral capsid antigen (sVCA) homologue from the rhesus LCV and developed a peptide enzyme-linked immunosorbent assay (ELISA) to determine whether epitopes in the rhesus LCV sVCA are a reliable indicator of rhesus LCV infection. In order to define a “gold standard” for rhesus LCV infection, we also cloned the EBV-encoded small RNA 1 (EBER1) and EBER2 homologues from rhesus LCV and developed a reverse transcription (RT)-PCR assay to detect persistent LCV infection in rhesus monkey peripheral blood lymphocytes. Animals from a conventional and a hand-reared colony were studied to compare the prevalence of rhesus LCV infection in the two groups. There was a 100% correlation between the peptide ELISA and EBER RT-PCR results for rhesus LCV infection. In addition, specificity for LCV infection and exclusion of potential cross-reactivity to the rhesus rhadinovirus sVCA homologue could be demonstrated using sera from experimentally infected animals. These studies establish two novel assays for reliable diagnosis of acute and persistent rhesus LCV infections. The rhesus LCV sVCA peptide ELISA provides a sensitive and reliable assay for routine screening, and these studies of the hand-reared colony confirm the feasibility of raising rhesus LCV-naive animals.